Fall Risk in Patients with Ankylosing Spondylitis - Hakan ALKAN; Necmettin YILDIZ; Ayşe SARSAN; Nilgün ŞİMŞİR ATALAY and Özgür SEVİNÇ and Oya TOPUZ and Füsun ARDIÇ (Archives of Rheumatology, 2013)
Objectives: The aim of this study was to investigate whether patients with ankylosing spondylitis (AS) have a higher fall risk than healthy subjects and to determine whether fall risk is associated with the clinical features of AS. Patients and methods: Forty AS patients (28 males, 12 females; mean age 37.20±9.92 years; range 20 to 60 years) who met the modified New York criteria and 40 age and gender-matched healthy controls were included. All participants were assessed by a static posturography device which provided numerical values in the percentage for fall risk. Patient interviews were used to assess the history of falls for the previous 12 months. The following tools were used for all AS patients: The Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) for disease activity, the Bath Ankylosing Spondylitis Functional Index (BASFI) for function, the Bath Ankylosing Spondylitis Metrology Index (BASMI) for spinal mobility, and the Ankylosing Spondylitis Quality of Life (ASQoL) questionnaire for quality of life. Results: There were no differences in the sociodemographic characteristics among the AS patients and the healthy controls (p>0.05). The mean fall risk was significantly higher for the AS patients compared to the controls (p<0.05). The ratio of AS patients who had a positive history of falls was significantly higher than controls (p<0.05). Fall risk was positively and significantly associated with the BASDAI (r=0.713, p<0.001), BASFI (r=0.751, p<0.001), BASMI (r=0.527, p<0.001), and ASQoL (r=0.627, p<0.001). The fall risk was not associated with the age, sex, body mass index and disease duration (p>0.05). Conclusion: Fall risk increased in patients with AS which was associated with poor spinal mobility, functional status, quality of life and higher disease activity. Increased risk of falling should be taken into consideration in the rehabilitation of the patients with AS.